Effect of Infiltration in Temporomandibular Joint with Triamcinolone Acetonide for Pain Relief in Internal Derangement - Ifra Tufail; Uzair Bin Akhtar; Ali Farooq; Salman Tariq; Sarah Zubair (Pakistan Journal of Health Sciences, 2026)
Orofacial pains are frequently caused by disorders of the temporomandibular joint (TMJ), which are often associated with masticatory difficulties, joint noises, and limited mouth opening. Despite the availability of several treatment options, a standardized management approach has yet to be developed. Intra-articular infiltration with Triamcinolone acetonide has been explored as a minimally invasive intervention for local symptomatic relief; clinical evidence regarding its effectiveness remains variable. Objective: To evaluate the effect of intra-articular triamcinolone acetonide injection on pain reduction in patients with TMJ internal derangement. Methods: A single-arm interventional pre–post study was performed on 71 patients with symptomatic TMJ internal derangement. Each patient received a local injection of 40mg/ml Kenacort (triamcinolone acetonide) under standard aseptic outpatient settings. The Wong-Baker FACES® Pain Rating Scale was employed to assess pain both before and one month following the intervention. Joint. Results: Among the 71 patients who reported pre-intervention pain, the mean pain score decreased from 6.085 to 2.423, and this change was statistically significant on paired t-testing (t=17.905, p